THE IMPACT OF ADOPTION OF ROOT AND TUBER EXPANSION PROGRAMME (RTEP) TECHNOLOGIES ON THE PRODUCTION AND INCOME CAPABILITIES OF FARMERS IN PLATEAU STATE - Ifeanyi, Okeh, Bernard; Atala, T.K.; Ahmed, B.; Omokore, D. (European Scientific Journal, ESJ, 2014)
The study was carried out in Plateau State in the year 2008-2010 to ascertain the impact of adoption of Root and Tuber Expansion Programme (RTEP) technologies on the production and income capabilities of farmers after the first phase of RTEP (2001 – 2004). The population of the study comprised all the 1020 registered RTEP farmers and the rest farmers not involved in RTEP. Proportional random sampling using 10% of participant farmers in each of the 5 Local Government Areas was used in selecting 102 Programme Participant Farmers (PPFs), while purposive sampling selection by chance of equal number of PPFs from each of the 5 local government areas was used in selecting 102 Non Programme Participant Farmers (NPPFs). Data collected by the use of structured questionnaire, were analyzed using descriptive statistics (mean, grand mean, standard deviation) and inferential statistics (t-test). The t-test analysis result revealed that there were differences between PPFs and NPPFs and even among PPFs in their production and income capabilities, it is recommended that RTEP should be enriched and designed to be attractive as to involve greater number of rural farmers so as to achieve greater influence on the production and income capabilities of the rural farmers in Plateau State.